Doença mental: aspectos históricos, sociais e jurídicos dos doentes mentais no sistema prisional do Estado do Amazonas - Bertazzo, Anagali Marcon (2016)
This work aims to study the historical, social and legal aspects of the mentally ill prison population in the State of Amazonas. Initially was performed the storyline of detention and incarceration and a research for the substantiation of the isolation imposed to the mentally ill. The prison system of the State of Amazonas and the recognition of a penitentiary law based on the pen delivery system were analyzed, this one symbolizing a hybrid result of judicial and administrative procedures. Among the assignments of both procedures, enable proper treatment of prisoners with mental disorders is required, both within the prison system as after the end of serving the sentence or security measure, ensuring the implementation of International standards for the recognition of human rights. Therefore, the prison population identified with mental illness and aspects such as the incidence of cases, age, gender, number of procedures in progress were evaluated in order to reach the description of a profile of those prisoners and inpatients in the prison system.